2017
DOI: 10.1136/bcr-2017-221837
|View full text |Cite
|
Sign up to set email alerts
|

Amyand’s hernia detected incidentally in two patients

Abstract: The appendix is rarely present inside the inguinal hernia sac. The risk of appendicitis increases in these patients since the blood supply to the appendix can be impaired. The condition is frequently asymptomatic, and even if symptomatic it gives rise to non-specific symptoms. There is no specific laboratory finding. Diagnosis is frequently made with radiological imaging. We report two cases diagnosed as Amyand's hernia with CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The ideal profile of the patient with an Amyand's hernia is a male subject, over 60 years old with a right sided mass (either palpable or not) [8 , 9 , 10] . However, some studies have reported the existence of this type of hernia in children with a prevalence of 1% [2 , 4] .…”
Section: Discussionmentioning
confidence: 99%
“…The ideal profile of the patient with an Amyand's hernia is a male subject, over 60 years old with a right sided mass (either palpable or not) [8 , 9 , 10] . However, some studies have reported the existence of this type of hernia in children with a prevalence of 1% [2 , 4] .…”
Section: Discussionmentioning
confidence: 99%